ANALYSIS AND ASSESSMENT OF NPP EXPOSURE TO NATURAL TECHNOGENIC EMERGENCY SITUATIONS - Yury I. Bulygin; Irina V. Bogdanova; Tatyana S. Guba; Svetlana Y. Aspidova (Advanced Engineering Research, 2012)
On the basis of the gathered statistics on the NPP accidents and earthquakes all over the world, the correlative relationship (according to Pearson criterion) between the NPP accident risks and natural technogenic ES risks effecting the stability and operation safety of such highly dangerous installations is revealed. The prognostic calculation during risk events from Poisson’s law is made. It is found that the correlation relationship power between earthquakes and NPP accidents is mean, and so the recurrence of such events in the future is probable.